Host-directed therapy for bacterial infections -Modulation of the phagolysosome pathway- - Taya, Toshihiko; Teruyama, Fumiya; Gojo, Satoshi (Frontiers in Immunology, 2023)
Bacterial infections still impose a significant burden on humanity, even though antimicrobial agents have long since been developed. In addition to individual severe infections, the f fatality rate of sepsis remains high, and the threat of antimicrobial-resistant bacteria grows with time, putting us at inferiority. Although tremendous resources have been devoted to the development of antimicrobial agents, we have yet to recover from the lost ground we have been driven into. Looking back at the evolution of treatment for cancer, which, like infectious diseases, has the similarity that host immunity eliminates the lesion, the development of drugs to eliminate the tumor itself has shifted from a single-minded focus on drug development to the establishment of a treatment strategy in which the de-suppression of host immunity is another pillar of treatment. In infectious diseases, on the other hand, the development of therapies that strengthen and support the immune system has only just begun. Among innate immunity, the first line of defense that bacteria encounter after invading the host, the molecular mechanisms of the phagolysosome pathway, which begins with phagocytosis to fusion with lysosome, have been elucidated in detail. Bacteria have a large number of strategies to escape and survive the pathway. Although the full picture is still unfathomable, the molecular mechanisms have been elucidated for some of them, providing sufficient clues for intervention. In this article, we review the host defense mechanisms and bacterial evasion mechanisms and discuss the possibility of host-directed therapy for bacterial infection by intervening in the phagolysosome pathway.